The distributional effects of austerity measures: A comparison of six EU countries - Tim Callan; Chrysa Leventi; Horacio Levy; Manos Matsaganis; Alari Paulus; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2011)
We compare the distributional effects of austerity measures that have been introduced in 6 EU countries in the period of large government budget deficits following the 2007-8 financial crisis and subsequent economic downturn. We explore the effects of policy changes presented as austerity measures in Estonia, Ireland, Greece, Spain, Portugal and the UK, using the EU microsimulation model EUROMOD and the Irish national model, SWITCH. The six countries have chosen different policy mixes to achieve varying degrees of fiscal consolidation. We focus on the first round effects of increases in personal taxes, cuts in spending on cash benefits and reductions in public sector pay across the distributions of household income. There is a range of important conceptual and consistency issues to be addressed when doing such analysis, particularly in a comparative setting. These include how to identify austerity measures in a consistent manner, the relevant time periods to consider, the assumptions behind the counterfactual scenarios and the scope of the policies considered. Using a set of common assumptions we find that the burden of fiscal consolidation brought about through changes in components of household disposable income is shared differently across the income distribution in the six countries. At one extreme, in Greece, the better off lose a higher proportion of their incomes than the poor and at the other, in Portugal, the poor lose a higher proportion than the rich. Bringing increases in indirect taxes into the picture can alter conclusions about the overall distributional effect, increasing the cost most for those with lower income and making the overall incidence of the measures more regressive.
Keywords: C81; H55; I3; 330; Austerity measures; European Union; Fiscal consolidation; Poverty; Microsimulation